Institutional barriers to the development of a comprehensive ballast-water management scheme in China: Perspective from a multi-stream policy model. (May 2018) - Wan, Zheng; Chen, Jihong; Sperling, Dan
Abstract: Millions of tons of ballast water are released into Chinese waters annually that could contribute a significant invasion vector in the country's marine ecosystem. While some endeavors have been made to assess and mitigate the impact, a comprehensive ballast water management scheme with focus on invasive aquatic species prevention has yet to be formulated on the state level. The policy and politics behind the ballast-water management in China are empirically investigated, focusing specifically on why the scheme failed to evolve and be reformed. Kingdon's multi-stream model was applied with an analytic lens on the problem stream, policy stream, and politics stream. The analysis was aided by public and internal documents related to ballast-water issues, and interviews with people familiar with the issue or who were stakeholders in the issue. Kingdon's model enables the identification of institutional barriers to the development of a comprehensive ballast-water management scheme with focus on invasive aquatic species prevention in China. Policy implications and recommendations are proposed for policy entrepreneurs who could initiate a change to the existing policy. Highlights: Millions of tons of ballast water are released into Chinese waters without proper supervision. A comprehensive ballast water management scheme with focus on invasive aquatic species prevention is lacking in China. Kingdon's multi-stream model was applied to understand the policy process behind the current fragmented scheme. Institutional barriers to the development of a comprehensive ballast-water management scheme were identified. Policy implications and recommendations are proposed for policy entrepreneurs.